2018
DOI: 10.7554/elife.39786
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine neuron glutamate cotransmission evokes a delayed excitation in lateral dorsal striatal cholinergic interneurons

Abstract: Dopamine neurons have different synaptic actions in the ventral and dorsal striatum (dStr), but whether this heterogeneity extends to dStr subregions has not been addressed. We have found that optogenetic activation of dStr dopamine neuron terminals in mouse brain slices pauses the firing of cholinergic interneurons in both the medial and lateral subregions, while in the lateral subregion the pause is shorter due to a subsequent excitation. This excitation is mediated mainly by metabotropic glutamate receptor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 72 publications
(113 reference statements)
0
61
0
Order By: Relevance
“…It is known that dopamine alters the input resistance of MSNs in vivo (Ketzef et al, 2017). Therefore, distinct dopaminergic innervation of the DLS-and DMS-MSNs (Chuhma et al, 2018) could underlie our differences in resistance between striatal regions.…”
Section: Integration Of the Spontaneous Activity In The Direct And Inmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that dopamine alters the input resistance of MSNs in vivo (Ketzef et al, 2017). Therefore, distinct dopaminergic innervation of the DLS-and DMS-MSNs (Chuhma et al, 2018) could underlie our differences in resistance between striatal regions.…”
Section: Integration Of the Spontaneous Activity In The Direct And Inmentioning
confidence: 99%
“…Under anaesthesia, dopaminergic neurons of the Substantia Nigra discharge spontaneous action potentials, in tonic or burst firing mode (Aristieta et al, 2016;Brown et al, 2009). This dopaminergic activity could induce different effects on the SWO in DLS-and DMS-MSNs, either directly mediated by distinct dopaminergic projections (Brown et al, 2009) or indirectly by their varied impact on ChIs activity along the mediolateral axis (Chuhma et al, 2018). Finally, it has been recently shown that SOM corticostriatal interneurons modulate the MSNs activity from motor cortical areas (Melzer et al, 2017;Rock et al, 2016).…”
Section: Dls and Dms Are Two Different Functional Circuits In Mousementioning
confidence: 99%
See 1 more Smart Citation
“…Midbrain DA neurons are heterogeneous not only regarding their axonal projections but also their morphological (e.g. variable dendrite architecture), molecular (GABA and glutamate co-release) and electrophysiological properties (Wolfart et al, 2001;Neuhoff et al, 2002;Amendola et al, 2012;Tritsch and Sabatini, 2012;Henny et al, 2012;Chuhma et al, 2018). In addition, DA neurons can be excited by both rewarding and aversive stimuli, suggesting that DA neurons participate in distinct circuits mediating partially distinct functions (Lammel et al, 2014;Morales and Margolis, 2017) As previously mentioned, behavioral flexibility is mediated by prefrontal connections to the striatum.…”
Section: Iii3 Dopaminergic Afferencesmentioning
confidence: 99%
“…The functional properties and the emerging diversity of the midbrain dopamine (DA) system have been extensively studied across many different biological scales (Schultz, 2015;Watabe-Uchida et al, 2017). These differences range from the single-cell level, including diverging gene expression profiles (Kramer et al, 2018;Nichterwitz et al, 2016;Poulin et al, 2018;Saunders et al, 2018a;Tiklova et al, 2019), cellular and biophysical properties Lammel et al, 2008;Tarfa et al, 2017), as well as neurotransmitter co-release (Chuhma et al, 2018;Kim et al, 2015b;Tritsch et al, 2012;Zhang et al, 2015), up to different neural circuit affiliations (Beier et al, 2019;Beier et al, 2015;Lammel et al, 2012;Lerner et al, 2015;Menegas et al, 2015;Ogawa et al, 2014;Tian et al, 2016;Watabe-Uchida et al, 2012) and selective task engagement of DA subpopulations in awake behaving rodents (Dautan et al, 2016;de Jong et al, 2019;Duvarci et al, 2018;Gunaydin et al, 2014;Howe and Dombeck, 2016;Keiflin et al, 2019;Lammel et al, 2012;Matthews et al, 2016;Menegas et al, 2018;Menegas et al, 2017;Parker et al, 2016;Patriarchi et al, 2018;Saunders et al, 2018b;Vander Weele et al, 2018;Yang et al, 2018) and non-human primates …”
Section: Introductionmentioning
confidence: 99%